Pelatihan Pengelolaan Keuangan Amal Usaha Pemuda Muhammadiyah (Pimpinan Daerah Pemuda Muhammadiyah Serdang Bedagai) - Salman Nasution; Muhammad Firza Alpi; Muhammad Teddy Nasution (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
The service carried out begins with a problem that occurs in businesses, especially Micro, Small and Medium Enterprises or abbreviated as MSMEs. As a youth organization and has an entrepreneurship work program, the Serdang Bedagai Muhammadiyah Youth is not left behind in owning MSMEs. Not a few MSMEs that exist have stagnated financial conditions due to a lack of understanding of financial management. Basically, Serdang Bedagai Muhammadiyah Youth MSMEs are able to stand with the concept of manual or general financial management but not based on financial standards designed by the Accounting Standards Board – IAI on Accounting Standards for Micro, Small and Medium Entities. Financial management training is a tool for Muhammadiyah Youth MSMEs in Serdang Bedagai in increasing the spirit of entrepreneurship and having good and clear and accountable financial reporting.